Observations on selected characteristics of water and sediment at the open sea cage culture site of Asian seabass Lates calcarifer (Bloch) off Cochin, south-west coast of India - Prema, D.; Sobhana, K. S.; Laxminarayana, A.; Joseph, Imelda; Joseph, Shoji; Ignatius, Boby; Jeyabaskaran, R.; Nandakumar, A.; Khambadkar, L. R.; Anilkumar, P. S.; Shylaja, G.; Rao, G. Syda (Indian Journal of Fisheries, 2011)
Study was undertaken to assess the impact of open sea cage culture of Asian seabass Lates calcarifer on selected parameters of water as well as sediment at Munambam off Cochin, Kerala coast from November 2008 to March 2009. Periodic observations were made on temperature, pH, dissolved oxygen, salinity, nutrients (NO3, PO4, SiO3), nitrite, ammonia, BOD, total suspended solids, chlorophyll a, gross and net primary productivity as well as bacterial load of the surface and near bottom water from the cage site (N 10Âº 08’ 162’’; E 76Âº 08’ 901’’) and also from a reference site (N 10Âº 07’ 189’’; E 76Âº 09’ 210’’) during pre- as well as post-stocking periods. Sediment samples were collected simultaneously from both the sites and analysed for texture, pH, organic carbon and bacterial load. A significant reduction (p<0.05) in silicate and chlorophyll a was perceived in surface water at the cage site, during the culture period as compared to pre-stocking period. No significant variations were noticed in any of the other parameters studied. The sand, silt, clay and organic carbon content in sediment at cage site differed significantly (p<0.05) from that of the reference site. There was no significant difference in the mean values of total heterotrophic bacterial count as well as presumptive Vibrio count of the water and sediment, either between the cage site and reference site or between the pre- and post-stocking samplings. No adverse effect as influenced by cage culture of fish was observed on any of the environmental parameters studied during the period of investigation.